Kirkeby's English?Swahili Dictionary - James S. Mdee (Lexikos, 2011)
Abstract: Kirkeby's English–Swahili Dictionary is a bilingual dictionary of more than 50 000entries. The most laudable feature of the dictionary is its attempt to be user-friendly especially inthe way the entry words have been arranged and the amount of information given. However, aclear objective for the compilation of the ditionary is lacking. The compilers do not seem to knowthe lexicographical gap they want to fill, the users they are targeting, and their dictionary-usingskills. In discussing the strong and weak points of the dictionary, the article will refer to theories ofdictionary criticism. Three criteria set by McMillan (1949) will guide this review article: (1) thequantity of the information in the dictionary; (2) the quality of the information presented; and (3)the effectiveness of the presentation of the information. Questions posed in the course of this articlewill include: Does the dictionary give the information required by the user? Is the informationtransparently accessible? How is the information presented? Keywords: DICTIONARY EVALUATION, USER-FRIENDLY, DICTIONARY-USINGSKILLS, LEXICOGRAPHICAL ENTRIES, GRAMMATICAL CATEGORIES, SUBGRAMMATICALCATEGORIES, WORD COMBINATIONS, COLLOCATIONS, TRANSLATION EQUIVALENTS Opsomming: Kirkeby se English–Swahili Dictionary. Kirkeby se English–SwahiliDictionary is 'n tweetalige woordeboek met meer as 50 000 inskrywings. Die mees prysenswaardigekenmerk van die woordeboek is sy poging om gebruikersvriendelik te wees, veral deur die manierwaarop die trefwoorde gerangskik is en die hoeveelheid inligting wat verskaf word. 'n Duidelikedoelwit vir die samestelling van die woordeboek ontbreek egter. Die samestellers is skynbaaronseker oor die leksikografiese leemte wat hulle wil vul, en die gebruikers vir wie dit bedoel is enhul woordeboekgebruikersvaardighede. In die bespreking van die sterk en die swak eienskappevan die woordeboek sal die artikel verwys na teorieë van woordeboekkritiek. Die kriteria gesteldeur McMillan (1949) sal as gids dien vir hierdie resensieartikel: (1) die hoeveelheid inligting in diewoordeboek; (2) die gehalte van die inligting aangebied; en (3) die doeltreffendheid van die aanbiedingvan die inligting. Vrae wat in die loop van hierdie artikel gestel sal word, sluit in: Gee diewoordeboek die inligting wat deur die gebruiker verlang word? Is die inligting deursigtig beskikbaar?Hoe word die inligting aangebied? Sleutelwoorde: WOORDEBOEKBEOORDELING, GEBRUIKERSVRIENDELIK, WOORDEBOEKGEBRUIKSVAARDIGHEDE,LEKSIKOGRAFIESE INSKRYWINGS, GRAMMATIKALEKATEGORIEË, SUBGRAMMATIKALE KATEGORIEË, WOORDVERBINDINGS, KOLLOKASIES,VERTAALEKWIVALENTE